The Peculiarity of Civil Liability for Errors of Artificial Intelligence in the Banking Sector under Omani Legislation - Abdullah, Murtadha Abdullah Khairi; Qashta , Nizar (Journal of Ecohumanism, 2024)
Objective: This study aims to highlight the issues of civil liability resulting from errors in AI banking applications. To date, there is ambiguity about whether it is possible to grant virtual legal personality to AI systems. Methodology: The researcher used the analytical method to understand the mechanisms of AI applied in banking operations, assess the effectiveness of these applications, and analyze the legal texts. Additionally, the inductive method was employed to fit the uses of AI in the banking sector. Results: The main findings of the study can be summarized as follows: The possibility of assigning civil liability to AI entities for errors they commit is applicable only in one case, which is when the AI banking system is the tool causing the damage. Conclusion: The study concludes that there is a need to amend certain legal texts in the Transactions Law. The study suggests that the Omani Civil Transactions Law of 2013 should be updated to align with the nature of AI in banking. This includes developing general legal rules related to the responsibility of employers for the actions of their employees and the custody of objects, ensuring they fit the specific errors of AI in banking. The study also provides some recommendations and proposals regarding the particularities of civil liability in the field of AI banking.